Papillomavirus can be transmitted through the blood and produce infections in blood recipients: Evidence from two animal models. Issue 1 (1st January 2019) - Cladel, Nancy M.; Jiang, Pengfei; Li, Jingwei J.; Peng, Xuwen; Cooper, Timothy K.; Majerciak, Vladimir; Balogh, Karla K.; Meyer, Thomas J.; Brendle, Sarah A.; Budgeon, Lynn R.; Shearer, Debra A.; Munden, Regina; et al.
ABSTRACT: Human papillomaviruses (HPV) contribute to most cervical cancers and are considered to be sexually transmitted. However, papillomaviruses are often found in cancers of internal organs, including the stomach, raising the question as to how the viruses gain access to these sites. A possible connection between blood transfusion and HPV-associated disease has not received much attention. Here we show, in rabbit and mouse models, that blood infected with papillomavirus yields infections at permissive sites with detectable viral DNA, RNA transcripts, and protein products. The rabbit skin tumours induced via blood infection displayed decreased expression of SLN, TAC1, MYH8, PGAM2, and APOBEC2 and increased expression of SDRC7, KRT16, S100A9, IL36G, and FABP9, as seen in tumours induced by local infections. Furthermore, we demonstrate that blood from infected mice can transmit the infection to uninfected animals. Finally, we demonstrate the presence of papillomavirus infections and virus-induced hyperplasia in the stomach tissues of animals infected via the blood. These results indicate that blood transmission could be another route for papillomavirus infection, implying that the human blood supply, which is not screened for papillomaviruses, could be a potential source of HPV infection as well as subsequent cancers in tissues not normally associated with the viruses.